Representasi Budaya Banyuwangi Dalam Banyuwangi Ethno Carnival: Pendekatan Teori Representasi Stuart Hall - Indah Mar’atus Sholichah; Dyah Mustika Putri; Akmal Fikri Setiaji (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
This article aims to analyze the cultural representation of Banyuwangi in the Banyuwangi Ethno Carnival (BEC) using Stuart Hall's representation theory approach. The main concepts applied in this analysis are change and resistance, which are used to understand how cultural symbols are represented and interpreted in BEC. The data collection process was carried out through a literature study. Where the data obtained comes from the results of research and other people's scientific works that are studied and then developed. Data analysis was carried out by combining Stuart Hall's representation theory concepts with the findings found in the BEC program. The results of the analysis of the literature study show that BEC is an important vehicle for representing Banyuwangi's cultural identity through modifications of costumes, dances, music, and other performances. In addition, the media plays an important role in the spread and influence of these cultural representations. In the context of Stuart Hall's representation theory, change refers to the transformation of cultural symbols in BEC, while resistance describes the process of building cultural representations through interactions and agreements between BEC actors, government and society. Through this process, Banyuwangi's cultural identity is represented and interpreted in the BEC event. The implication of the results of this research is the need for continuous support in developing and promoting Banyuwangi culture through collaborative efforts between the government, cultural actors and the community. In this case, BEC can be an effective tool to strengthen and broaden understanding and appreciation of Banyuwangi's cultural identity